Perubahan Landscape Ekonomi Wilayah (Studi Kasus Pendekatan Historical Input-Output di Jawa Timur) - Muhammad Alwan Habibi Mushlih; Teguh Hadi P; Fajar Wahyu P (Trunojoyo University of Madura, 2018)
Industrialization grew fast in East Java after 1998 crisis and can be look at the first position of the easy of doing business category year 2017 by the Asia Competiveness Institute. This study aims to determine the pattern of economic landscape in East Java by using the input-output table which is then analyzed into various tables derived from the input-output itself. Structural changes occurred in East Java during the period 2000 to 2015 which is shown by changes in economic landscape. This change can be seen in the Multiplier Product Matrix (MPM). In 2000 the highest MPM value was in 2000 the highest MPM value was mining and quarrying sector with other industrial sector with MPM value equal to 0,1247. In 2006 the highest MPM value is fishery sector with trade sector with MPM value equal to 0,11012. In 2010 the highest MPM value of the livestock sector with the sector of financial institutions, building businesses, and services companies with MPM value of 0.141735. In 2015 the highest MPM value is the mining and quarrying sector with other industrial sectors with MPM value of 0.19426.